3.2k views
4 votes
Find the value of the following expression:

(2^8 ⋅ 3^−5 ⋅ 6^0)−2 * (3^-2 over 2^3)^4 * 2^28

Write your answer in simplified form. Show all of your steps

1 Answer

1 vote


image


\mathrm{Apply\:rule}\:a^0=1,\:a\\e \:0


6^0=1


=2^(28)\left((3^(-2))/(2^3)\right)^4\left(3^(-5)\cdot \:2^8\cdot \:1\right)^(-2)


\left(2^8\cdot \:3^(-5)\cdot \:1\right)^(-2)=\left(1\cdot (256)/(243)\right)^(-2)=\left((243)/(256)\right)^2


\left((3^(-2))/(2^3)\right)^4=(1^4)/(\left(2^3\cdot \:3^2\right)^4)=(1^4)/(3^8\cdot \:2^(12))


2^(28)\left((3^(-2))/(2^3)\right)^4\left(3^(-5)\cdot \:2^8\cdot \:1\right)^(-2)=(243^2\cdot \:1\cdot \:2^(28))/(256^2\cdot \:3^8\cdot \:2^(12))


=(2^(16)\cdot \:243^2)/(3^8\cdot \:256^2)


=(2^(16)\cdot \:3^(10))/(2^(16)\cdot \:3^8)


=3^2


=9

User FredericP
by
6.1k points